Crystal Growth Behaviors of Silicon during Melt Growth Processes - Kozo Fujiwara (International Journal of Photoenergy)
It is imperative to improve the crystal quality of Si multicrystal ingots grown by casting because they are widely used for solar cells in the present and will probably expand their use in the future. Fine control of macro- and microstructures, grain size, grain orientation, grain boundaries, dislocation/subgrain boundaries, and impurities, in a Si multicrystal ingot, is therefore necessary. Understanding crystal growth mechanisms in melt growth processes is thus crucial for developing a good technology for producing high-quality Si multicrystal ingots for solar cells. In this review, crystal growth mechanisms involving the morphological transformation of the crystal-melt interface, grain boundary formation, parallel-twin formation, and faceted dendrite growth are discussed on the basis of the experimental results of in situ observations.